Use of 3D laser scanning on evaluating reduction of initial geometric imperfection of steel column with pre-stressed CFRP. (1st November 2019) - Feng, Peng; Zou, Yichong; Hu, Lili; Liu, TianQiao
Highlights: A novel method for obtaining initial geometric imperfections by 3D scanning is presented and developed. The reducing initial geometric imperfections by PS CFRP strengthening is discovered and illustrated. A theoretical model is proposed and verified by comparing to the measurement results. Abstract: A novel method for obtaining initial geometric imperfections by three-dimensional (3D) laser scanning is developed to study a discovery of reducing initial geometric imperfections using pre-stressed (PS) carbon fiber reinforced polymer (CFRP) strips. New methodologies for establishing digital geometric models of specimens based on point cloud data are presented. The initial deflections along the weak axes of two series of specimens with I-shaped section, 10 specimens in total, are obtained by these methods. It is found that the initial deflections along the weak axes of the steel columns are reduced by the PS CFRPs. Then, the force method is implemented to establish a theoretical model for steel columns strengthened with PS CFRPs. The model illustrates the mechanism for decreasing geometric imperfections in a self-balanced process. Corresponding equations based on the theoretical model are proposed to explain the reduction of the initial deflections. Finally, the model is verified by comparing its predictions to the measurement results.